IMPACT OF ENTREPRENEURSHIP EDUCATION IN ENGINEERING COLLEGES TO BUILD SUCCESSFUL ENTREPRENEURS - K Jeevan Kumar; K Arjun Goud, (International Journal of Advances in Business and Management Research (IJABMR), 2025)
Examining how engineering college students' aspirations for business changed after receiving entrepreneurship instruction was the driving force for this study. The purpose of this study is to answer the question, "To what extent does college-level entrepreneurship education influence students' entrepreneurial attitude?" in order to determine students' attitudes and intents toward entrepreneurial education. A behavioural theory-supported conceptual model was used to understand the students' attitudes. Despite the increasing amount of research on the subject, many concerns about the impact of entrepreneurship courses at engineering schools remain unresolved. Very little research has focused on the Indian context, particularly how engineering schools there teach entrepreneurship in light of the local environment and socioeconomic conditions. There is a dearth of studies that compare the impact of different teaching approaches on entrepreneurial results, such as project-based learning vs lecture. A new approach to engineering college curricula is needed to foster an atmosphere that encourages the growth of entrepreneurial mindsets and practices.